Ferozsons urdu english dictionary (a Comprehensive Dictionary of Current Vocabulary) - Muhajir, Ali Musa Raza (Feroz sons Lahore, 1989)
The "Ferozsons Urdu English Dictionary (Revised Edition)" is a comprehensive reference work that provides a rich collection of Urdu words along with their English meanings and usage. This updated edition includes modern vocabulary, idiomatic expressions, and practical examples, making it an essential tool for students, writers, and professionals alike. Its clear layout and user-friendly format facilitate easy navigation, helping users enhance their language skills in both Urdu and English. This dictionary remains a trusted resource for anyone looking to improve their bilingual communication and understanding.